Performance Analysis of Interleaved Quadratic Boost Converter with Coupled Inductor for Fuel Cell Applications - Balci, Selami; Altin, Necmi; Komurcugil, Hasan; Sefa, Ibrahim (IEEE, 2016)
DC-DC converters are commonly used in many fields such as renewable energy sources, electrical vehicles, power supplies, battery chargers and fuel cell applications. These converters are used for purposes such as voltage conditioning, regulation of their outputs, obtaining maximum power and providing isolation. In practice, various criteria such as cost, performance, efficiency and size are considered while converter topology is determined. Filter components (LC) which are used in DC-DC converter determine the converter size. In this study, an interleaved quadratic boost converter is designed for fuel cell applications and different inductor designs are investigated for the proposed quadratic boost converter. Four different inductor models are designed and simulation studies of the interleaved quadratic boost converter with these inductor models are carried out. Effects of the designed inductors on converter output waveform quality, total weight and volume, and converter efficiency are investigated and obtained results are compared. It is seen from obtained results that, the coupled inductor improves performance and efficiency of the interleaved quadratic boost converter.
42nd Annual Conference of the IEEE-Industrial-Electronics-Society (IECON) -- OCT 24-27, 2016 -- Florence, ITALY
Keywords: Quadratic boost converter; Fuel cell; Interleaved converter; Coupled inductor design; FEA